Evaluation of STEM students’ critical thinking in terms of cognitive style through problem-based distance learning - Lubna; Suhirman; Prayogi, Saiful (Journal of Education and e-Learning Research, 2023)
The advent of digital technology has brought about a transformation in the field of education, from traditional face-to-face learning to distance learning. Despite this shift, it is important to prioritize the development of STEM (Science, Technology, Engineering, and Math) students’ critical thinking (CT) abilities as an essential skill for success in the 21st century. The objective of this study is to assess the critical thinking (CT) skills of students in the fields of science, technology, engineering, and mathematics (STEM) by considering their cognitive styles, namely field-independent and field-dependent, through the implementation of Problem-Based Distance Learning (PBDL). The research follows an evaluative and experimental approach based on the Kirkpatrick four-level model, which was conducted at one of the universities providing STEM education in eastern Indonesia. To evaluate different components of learning, cognitive style, and critical thinking (CT), a wide range of tools with tested psychometric features (validity and reliability) were used. A comprehensive examination using both descriptive and statistical analyses was undertaken to evaluate the outcomes. The results of this study indicate that Problem-Based Distance Learning (PBDL) is a successful approach in enhancing the Critical Thinking (CT) skills of STEM students, irrespective of their cognitive types. The paper provides a detailed discussion of the thorough examination of input, process, output, and outcome factors. This study is very valuable and will contribute to a lot of literature, especially related to the development of distance pedagogy in STEM learning.